Obstructive jaundice of rare origin in a six years old girl. - Chavarría, Oscar; Benedictti, Juan Luis (Cirugía del Uruguay, 1989)
An hydatic cyst of the head of the pancreas in a 6 years .old girl is presented. Symptomatology as well as auxiliary diagnostic tests now avallable are analyzed. Finally we enumerate the differents operative procedures accepted